2009
DOI: 10.1089/end.2008.0605
|View full text |Cite
|
Sign up to set email alerts
|

Selective Versus Nonselective Arterial Clamping During Laparoscopic Partial Nephrectomy: Impact upon Renal Function in the Setting of a Solitary Kidney in a Porcine Model

Abstract: Diaz, Dilmer L.; Maxwell, Keegan L.; Badwan, Khalid H.; Talcott, Michael R.; Liapis, Helen; Cabello, Jose M.; Venkatesh, Ramakrishna; and Figenshau, Robert S., ,"Selective versus nonselective arterial clamping during laparoscopic partial nephrectomy: Impact upon renal function in the setting of a solitary kidney in a porcine model." Journal of Endourology.23,7. 1127Endourology.23,7. -1133Endourology.23,7. . (2009 Introduction: Laparoscopic partial nephrectomy has emerged as a standard of care for small renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 22 publications
1
30
0
2
Order By: Relevance
“…Viprakasit and colleagues 26 described successful use of this technique in three patients undergoing RAPN. 26 We previously reported improved renal functional outcomes with segmental rather than complete hilar clamping in a porcine model 27 and demonstrated the safety and feasibility of this technique in humans. 28 More recently, some surgeons have performed PN without any clamping of the renal hilum and have suggested that off-clamp PN can be safely performed in carefully selected patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Viprakasit and colleagues 26 described successful use of this technique in three patients undergoing RAPN. 26 We previously reported improved renal functional outcomes with segmental rather than complete hilar clamping in a porcine model 27 and demonstrated the safety and feasibility of this technique in humans. 28 More recently, some surgeons have performed PN without any clamping of the renal hilum and have suggested that off-clamp PN can be safely performed in carefully selected patients.…”
Section: Discussionmentioning
confidence: 91%
“…Of note, this technique represents an evolution in our efforts to minimize WIT, building on our previous experience with segmental arterial clamping. 27,28 In the short-term, a minimal and statistically insignificant decline in renal function was seen after off-clamp RAPN. The mean EBL (210 mL) and operative time (143 min) were clinically appropriate, and all surgical margins were negative for tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Хорошей альтернативой традиционным методам противо-ишемической защиты является селективное вы-ключение кровотока в опухолевом узле или в содер-жащем его сегменте почки. Эффективность такого подхода при лапароскопических операциях была продемонстрирована в эксперименте на животных [15]. В последнее время появились первые, но весь-ма обнадеживающие сообщения об использовании локальной ишемии при лапароскопической резек-ции почки в клинике [7].…”
Section: результаты и обсуждениеunclassified
“…Selective arterial clamping is a recent technique that had undergone evaluation in porcine models [24]. In this technique, only the segmental artery supplying the tumour was clamped.…”
Section: Techniques To Lessen Ischaemic Damage or Ischemia Timementioning
confidence: 99%